2000
DOI: 10.1177/089198870001300205
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Syndromes and Functional Disability in Dementia

Abstract: The goals of this study were to assess (1) the prevalence of major and minor depression in Alzheimer's disease (AD), ischemic vascular dementia (IVD), and mixed dementia (AD/IVD); (2) demographic and clinical variables that may be associated with depression; and (3) the relationship between depression severity and the level of functional impairment and cognitive decline. Demographic variables, depression diagnoses, Mini-Mental State Examination scores, and Blessed Roth Dementia Rating Scale scores were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 39 publications
4
35
1
Order By: Relevance
“…Depression may be an early sign of Alzheimer's disease or an increased risk to Alzheimer's disease Cognitive impairment is a significant predictor for depressive symptoms (Minicuci et al 2002). It is reported that approximately 30 to 40 % of those who have dementia will develop depression in the course of their disease (Hargrave et al 2000). Depression can amplify cognitive impairment in the elderly (Boland 2000) and the combination of cognitive impairment and depression increases the odds of mortality and morbidity (Luis et al 2003).…”
Section: Disease Variablesmentioning
confidence: 99%
“…Depression may be an early sign of Alzheimer's disease or an increased risk to Alzheimer's disease Cognitive impairment is a significant predictor for depressive symptoms (Minicuci et al 2002). It is reported that approximately 30 to 40 % of those who have dementia will develop depression in the course of their disease (Hargrave et al 2000). Depression can amplify cognitive impairment in the elderly (Boland 2000) and the combination of cognitive impairment and depression increases the odds of mortality and morbidity (Luis et al 2003).…”
Section: Disease Variablesmentioning
confidence: 99%
“…Everyday action errors are a serious concern in dementia (Giovannetti, Libon, Buxbaum, & Schwartz, 2002;Giovannetti, Schwartz, & Buxbaum, 2007;Giovannetti et al, 2008). In fact, everyday action impairment is one of the diagnostic criteria of Alzheimer's disease and is associated with many serious consequences, including institutionalization, depression, and death (Adam, Van der Linden, Juillerat, & Salmon, 2000;Hargrave, Reed, & Mungus, 2000;Knopman, Kitto, Deinard, & Heiring, 1988;Noale et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Quite often, action errors pose negative consequences for employment and independent living in such high functioning populations (Asikainen, Kaste, & Sarna, 1996;Nadeau, 2005). In individuals with moderate to severe neuropsychological deficits, action performance may be more seriously impaired and linked to numerous negative outcomes, including institutionalization, depression, and death (Adam, van der Linden, Jullerat, & Salmon, 2000;Hargrave, Reed, & Mungus, 2000;Knopman, Berg, & Thomas, 1999;Noale, Maggi, & Minicuci, 2003). Studies by Schwartz and colleagues (Schwartz, Buxbaum, Montgomery, Lee, & Coslett, 1999;Schwartz et al, 1998) have shown that action deficits in moderately to severely impaired neuropsychological populations may be best understood as an exaggeration of the normal tendency to commit errors of action in states of fatigue or distraction, when cognitive resources are diminished.…”
Section: Introductionmentioning
confidence: 99%